Aplikasi Sistem Laporan Kerja Harian Staf Pelayanan PT. Securindo Packatama Indonesia Berbasis Web dengan Metode Rapid Application Development - Moch Fikri; Panser Karo-Karo; NM Faizah (Design Journal, 2024)
This study aims to develop a web-based daily work report information system that is more effective, efficient, and computerized. The application is designed to assist service staff in preparing daily reports and provides a data backup medium for work programs. The study employs the Rapid Application Development (RAD) method, which emphasizes fast development through iterative prototyping and active user involvement. RAD consists of several phases, including planning, design workshops, and implementation, allowing continuous user feedback to incrementally improve the system. Data was collected through field studies with direct observation, discussions with colleagues, and interviews with relevant parties. The application was built using PHP and MySQL and tested comprehensively to ensure performance and accuracy. The study concludes that the system effectively facilitates report recapitulation and performance data presentation, improving operational efficiency at PT. Securindo Packatama Indonesia.